Networks and (inter)relations: The social organization of fish farming in Maripá/PR (Research, Society and Development, 2021)
Paraná is the Brazilian state that has emerged as the largest Brazilian producer of fish farming. The west of Paraná, especially the municipality of Maripá, contributes significantly to this result. In this sense, the objective was to understand the aspects of this promotion of fish farming in the city of Maripá/PR. The theory discussed was of social capital, of Bordieu and Putnam, and its relation with development; then, admitted the link between social relations and economic development, of Bresser-Pereira. The methodology: Initially, we sought to identify the variables presented in previous studies; Then, for the sampling of results, was entered the theory of strong and weak ties, of Granovetter, with use of Analysis of Social Networks (ARS), of Marteleto; and graphic diagramed using the Ucinet® software. The considerations: The fish farming chain agents (industries, producers, markets, universities, regulators, assistance and credit agencies, among others) from Maripá established strategies of development based on dimensions of social capital (trust, conduct, rights and obligations institucions, among others). However, yet there is need for a sustainable see inboard, about of institutional behavior to environment.